Secular Trends on Birth Parameters, Growth, and Pubertal Timing in Girls with Turner Syndrome - Woelfle, Joachim; Lindberg, Anders; Aydin, Ferah; Ong, Ken K.; Camacho-Hubner, Cecilia; Gohlke, Bettina (Frontiers in Endocrinology, 2018)
Background: Whether children with chromosomal disorders of growth and puberty are affected by secular trends (STs) as observed in the general population remains unanswered, but this question has relevance for expectations of spontaneous development and treatment responses. Objectives: To study STs in birth parameters, growth and pubertal development in girls with Turner syndrome (TS). Study design: Retrospective analysis of KIGS data (Pfizer International Growth Database). We included all TS patients who entered KIGS between 1987 and 2012 and were born 1975 to 2004, who were pre-pubertal and growth-treatment naïve at first entry (total number: 7219). Pre-treatment height and ages at treatment start were compared across 5-year birthyear groups, with sub-group analyses stratified by induced or spontaneous puberty start. Results: We observed significant STs across the birthyear groups for birth weight (+0.18 SDS, p<0.001), pre-treatment height at mean age 8 years (+0.73 SDS, p<0.001), height at start of GH-therapy (+0.38 SDS, p<0.001) and start of puberty (+0.42 SDS, p<0.001). Spontaneous puberty onset increased from 15% to 30% (p<0.001). Mean age at GH treatment start decreased from 10.8 to 7.4 years (-3.4 years; p<0.001), substantial declines were seen in ages at onset of spontaneous and induced puberty (-2.0 years; p<0.001) and menarche (-2.1 years; p<0.001). Conclusion: Environmental changes leading to increased height and earlier, and also more common, spontaneous puberty are applicable in TS as in normal girls. In addition, greater awareness for TS may underlie trends to earlier start of GH therapy and induction of puberty at a more physiological age.